Hubungan konsumsi makanan junk food dan tingkat depresi pada remaja dan dewasa muda - Waviq Aziza; Tri Siswati; Weni Kurdanti (UHAMKA PRESS, 2026)
Depression among adolescents and young adults is often associated with psychosocial stress and unhealthy lifestyles, including poor dietary patterns such as frequent junk food intake. This study aimed to analyze the correlation between junk food consumption and depression levels among adolescents and young adults in Argosari Village, Bantul. This study was a cross-sectional investigation conducted among 64 adolescents and young adults, selected using purposive sampling. Junk food consumption was assessed with a Food Frequency Questionnaire (FFQ), while depression levels were measured using the Beck Depression Inventory II (BDI-II). The data were analyzed using the Chi-square test. The results showed that most subjects consumed junk food quite frequently (40.6%), followed by rarely (35.9%), and frequently (23.4%). The distribution of depression levels was as follows: minimal (34.4%), mild (37.5%), moderate (21.9%), and severe (6.3%). Bivariate analysis showed that adolescents and young adult who rarely consumed junk food mostly experienced minimal or mild depression (82.6%), while those with frequent consumption had higher proportions of moderate to severe depression (50%). The Chi-square test confirmed a significant correlation between junk food consumption and depression levels (p=0.042). The conclusion is that higher junk food consumption was significantly associated with higher levels of depression among adolescents and young adults. These findings highlight the importance of promoting balanced dietary habits as part of adolescent and young adult mental health prevention strategies.